(untitled) (Proceedings of Southern Federal University. Philology, 2018)
Alexey A. Chukhno (Rostov-on-Don, Russian Federation) This article is devoted to the study of linguistic features of online sports commentary. It gives a brief description of online sports commentary and focuses on the most common lexical and grammatical peculiarities found through analysis of several online commentaries of football matches published on two most viewed and popular foreign websites. Key words: online sport commentary, lexical and grammatical peculiarities, text translation, internet-communication.